Noncoding RNAs Involved in Mammary Gland Development and Tumorigenesis: There’s a Long Way to Go - Shore, Amy N.; Herschkowitz, Jason I.; Rosen, Jeffrey M. (Journal of mammary gland biology and neoplasia, 2012)
The mammalian genome encodes thousands of noncoding RNAs. These noncoding transcripts are broadly categorized into short noncoding RNAs, such as microRNAs (miRNAs), and long noncoding RNAs (lncRNAs) of greater than 200 nt. While the role of miRNAs in development and cancer biology has been extensively studied, much less is known about the vast majority of noncoding transcripts represented by lncRNAs. LncRNAs are emerging as key regulators of developmental processes and as such, their frequent misregulation in tumorigenesis and disease in not unexpected. The role of lncRNAs in mammary gland development and breast cancer is just beginning to be elucidated. This review will discuss the role of lncRNAs in mammalian and mammary gland development. In addition, we will review the contributions of lncRNAs to the stepwise progression of tumorigenesis, highlighting the role of lncRNAs in breast cancer.